A-Z of Neurological Practice, Second Edition A Guide to Clinical Neurology - Larner, Andrew J.; Coles, Alasdair J.; Scolding, Neil J.; Barker, Roger A.; SpringerLink (Online service) (London : Springer London, 2011)
The Second Edition of A-Z of Neurological Practice builds on the previous edition with revised and updated information in a high density but easily accessible format to provide a quick and ready reference for busy clinicians of all degrees of experience. Entries for specific neurological conditions are uniformly structured indicating: Pathophysiology; Clinical Features; Investigations and Diagnosis; Differential Diagnosis; Treatment and Prognosis. Key references are cited throughout and all entries are cross referenced.
Keywords: Medicine; Emergency medicine; Neurology; Medicine & Public Health; Neurology; Emergency Medicine